Sit-stand workstations: A pilot intervention to reduce office sitting time - Alkhajah, T.; Reeves, M.; Eakin, E.; Winkler, E.; Owen, N.; Healy, Genevieve (2012)
Background: Sitting time is a prevalent health risk among office-based workers. Purpose: To examine, using a pilot study, the efficacy of an intervention to reduce office workers' sitting time. Design: Quasi-experimental design with intervention-group participants recruited from a single workplace that was physically separate from the workplaces of comparison-group participants. Setting/participants: Office workers (Intervention, n=18; Comparison, n=14) aged 20–65 years from Brisbane, Australia; data were collected and analyzed in 2011. Intervention: Installation of a commercially available sit–stand workstation. Main outcome measures: Changes from baseline at 1-week and 3-month follow-up in time spent sitting, standing, and stepping at the workplace and during all waking time (activPAL3 activity monitor, 7-day observation). Fasting total cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides, and glucose levels were assessed at baseline and 3 months (Cholestech LDX Analyzer). Acceptability was assessed with a 5-point response scale (eight items).